TRENDS KRIMINAL DI PEKANBARU 2012-2016 - Syahrul Akmal Latief; Fakhri Usmita; Riky Novarizal (UIR PRESS, 2017)
The least availability of criminal data for the community, makes it difficult to get a picture of the crime. This study aims to illustrate the trend of crime in Pekanbaru City in 2012-2016 by using a quantitative alignment in view of police criminal statistics in Pekanbaru. This study focuses on eight criminal acts, namely: theft of two-wheeled vehicles, theft by weight, maltreatment, narcotics abuse, embezzlement, domestic violence, motor vehicle theft, and deprivation. The results of this study indicate a fluctuation of crime rates for eight crimes under investigation. The crime total reached in 2014 was 928 cases, and relatively decreased for the following years. The average trend of increasing or decreasing crime amounted to 19.5 cases per year.